2020
DOI: 10.3390/nu12113407
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Status and Dietary Diversity of Women of Reproductive Age in Rural Pakistan

Abstract: Consuming a diverse diet is essential to ensure an adequate intake of micronutrients. The aim of this study was to assess the nutritional status and dietary diversity of women of reproductive age (WRA) living in a marginalized community in rural Pakistan. Forty-seven WRA (35 ± 7 years old) who were not pregnant or lactating at enrollment, were recruited to participate in the study. Twenty-four-hour dietary recall interviews were conducted by the study nutritionist, and the data collected were used to create a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 22 publications
5
26
0
Order By: Relevance
“…Based on the prevalence rate, anemia and iron deficiency are mild public health issues in this population group. These finding are similar to a recent study conducted in a resource poor community in the same area of Pakistan [ 38 ] but markedly different from the national nutrition survey of Pakistan [ 11 ] and other studies [ 39 ] that report anemia prevalence in >50% of the population. This was an unexpected finding as the routine dietary intake in these population groups include wheat as a staple food which is low in readily bioavailable heme iron [ 38 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Based on the prevalence rate, anemia and iron deficiency are mild public health issues in this population group. These finding are similar to a recent study conducted in a resource poor community in the same area of Pakistan [ 38 ] but markedly different from the national nutrition survey of Pakistan [ 11 ] and other studies [ 39 ] that report anemia prevalence in >50% of the population. This was an unexpected finding as the routine dietary intake in these population groups include wheat as a staple food which is low in readily bioavailable heme iron [ 38 ].…”
Section: Discussionsupporting
confidence: 78%
“…These finding are similar to a recent study conducted in a resource poor community in the same area of Pakistan [ 38 ] but markedly different from the national nutrition survey of Pakistan [ 11 ] and other studies [ 39 ] that report anemia prevalence in >50% of the population. This was an unexpected finding as the routine dietary intake in these population groups include wheat as a staple food which is low in readily bioavailable heme iron [ 38 ]. A possible reason to this might be the culinary practices in these population that involve use of iron-based cocking pots and utensils.…”
Section: Discussionsupporting
confidence: 78%
“…In a study of dietary diversity in a resource-poor setting in Pakistan, we reported that MMD-W was not achieved by most of the participants. This low diet diversity was associated with a high prevalence of zinc deficiency (measured using plasma zinc concentration), however, surprisingly, iron deficiency was not detected using established biomarkers (blood Hb and serum ferritin concentrations) (30) . This may have been due to the intake of iron from non-food sources, such as iron leached from the cooking pots.…”
Section: Increasing Dietary Diversitymentioning
confidence: 92%
“…The characteristics of the participants, including indicators of socioeconomic status, HH demographics and anthropometric measures of the participating WRA were collected at baseline. These have been reported previously along with dietary diversity data (24). In addition, blood samples were collected at each T to monitor health status throughout the study.…”
Section: Participant Characteristics and Haematologymentioning
confidence: 93%